Emphasis on Curriculum Contents in Civic Education for Secondary School in Nigeria - Sele , Anderson Paingha (South Asian Journal of Social Sciences and Humanities, 2020)
Civic Education is the study of the rights and responsibilities of citizens taught in many primary schools in some years back but have been replaced with citizenship education in some secondary schools in Nigeria. This paper highlights the reasons for Civic Education in Nigeria; as the country has moved from normative society to pluralistic society. This situation has created negative behavioral change which is noticeable in Nigeria today. The paper further outlines the blocks and topics which are adoptable as curriculum for Civic Education in Nigerian secondary schools and finally states some problems that may militate against the implementation of the curriculum. Educational practices in indigenous Nigeria had social content in which civic education was preponderant. The colonial educational outfit had a patchy civic education curriculum which was British culture-biased and, therefore, was not pertinent to our peoples’ aspirations. A little after independence on October 1, 1960, the pervasive colonial oriented education with its twist of colonial civic education curriculum was criticized and the result was a refashioning of curricula which became operational in schools from 1982 but in which civic education was completely shielded out. It was not until year 2007 that, the civic education curriculum for the 9-year Basic Education was born to exist pari-pasu with Social Studies curriculum. This paper, in drawing attention to the fact that civic education is, an unnecessary duplication of social studies curriculum in another garb, outlines the lapses in the Upper Basic Civic Education Curriculum and in addition raises seventeen (17) yet to be tackled queries. An immediate revision of the Civic Education Curriculum is recommended.